1983
DOI: 10.2307/1590209
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Reticuloendotheliosis Virus Infection in Ducks

Abstract: A new isolate of reticuloendotheliosis virus (REV) from ducks, RU-1, was used to experimentally infect white pekin ducks. Embryonal or neonatal infection usually resulted in persistent viremias, no REV antibody development, and inability to mount antibody responses against bovine serum albumin (BSA) or sheep red blood cells (SRBC). In contrast, infection at 21 days of age resulted in transient viremias, which terminated coincident with REV antibody development. These ducks remained persistently infected, howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…A study a few years later confirmed the presence of an additional “filterable agent”—the cause of a lethal anemia—in P. lophurae –infected poultry [30], and in 1959 William Trager identified this agent as SNV [28]. Subsequently, SNV-like viruses were isolated from P. lophurae –infected ducks on multiple distinct occasions (Table 2) [1],[31. The role of P. lophurae stocks as a source of infection appears to have gone unappreciated prior to the isolation of DIAV in 1972 [29].…”
Section: Discussionmentioning
confidence: 99%
“…A study a few years later confirmed the presence of an additional “filterable agent”—the cause of a lethal anemia—in P. lophurae –infected poultry [30], and in 1959 William Trager identified this agent as SNV [28]. Subsequently, SNV-like viruses were isolated from P. lophurae –infected ducks on multiple distinct occasions (Table 2) [1],[31. The role of P. lophurae stocks as a source of infection appears to have gone unappreciated prior to the isolation of DIAV in 1972 [29].…”
Section: Discussionmentioning
confidence: 99%
“…It is surprising that natural infection of ducks (e.g. Li et al, 1983) is reported so rarely, presumably a re¯ection of the inef® ciency of horizontal transmission. Using cells taken from organs of ducks infected with REV-T we have been able to establish lymphoblastoid cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Unstained sections were heated at 608C for 15 min and deparaffinized in Hemo-De (PMP Medical Industries) for 20 Isolated from a duck and provided by Dr K. A. Schat (see Li et al, 1983). b Isolated from frozen turkey tissue (see Crespo et al, 2002).…”
Section: Methodsmentioning
confidence: 99%